Murine genetic deficiency of neuronal nitric oxide synthase (nNOS‐/‐) and interstitial cells of Cajal (W/Wv): Implications for achalasia?. Issue 10 (October 2014) - Müller, Michaela; Colcuc, Sebastian; Drescher, Daniel G.; Eckardt, Alexander J.; von Pein, Harald; Taube, Christian; Schumacher, Johannes; Gockel, Henning R.; Schimanski, Carl C.; Lang, Hauke; Gockel, Ines
Abstract Background and Aim Nitric oxide (NO) is an important inhibitory mediator of esophageal function, and its lack leads to typical features of achalasia. In contrast, the role of intramuscular interstitial cells of Cajal (ICC‐IM) and vasoactive intestinal peptide (VIP) in lower esophageal sphincter (LES) function is still controversial. Therefore, we examined the function and morphology of the LES in vivo in NO‐deficient (nNOS‐/‐), ICC‐IM‐deficient (W/Wv)‐, and wild‐type (WT) mice. Methods Esophageal manometry was performed with a micro‐sized transducer catheter to quantify LES pressure, swallow evoked LES relaxation, and esophageal body motility. The LES morphology was examined by semiquantitative analysis of the immunoreactivity (reduction grade I–IV) of neuronal NOS (nNOS), ICC‐IM, and VIP and their correlation with esophageal function. Results nNOS‐/‐ in comparison to WT mice showed a significantly higher LES mean resting pressure with an impaired swallow induced relaxation, whereas W/Wv mice had a hypotensive LES with decreased relaxation. W/Wv and nNOS‐/‐ mice demonstrated differing degrees of tubular esophageal dysfunction. The reduced immunoreactivity of nNOS correlated with an increased LES pressure and decreased LES relaxation, respectively. Cajal‐cell reduction correlated with impaired LES relaxation, whereas VIP reduction revealed no correlation with esophageal function. Conclusions The reduction of ICC‐IM and nNOS can cause dysfunction of the LES and esophageal peristalsis, whereas VIP reduction seems to have no effect. ICC‐IM and nNOS deficiency might be independent relevant causes of esophageal dysfunction similar to that seen in human achalasia.